8051 Microcontrollers Fundamental Concepts, Hardware, Software and Applications in Electronics - Gimenez, Salvador Pinillos (Springer International Publishing : Imprint: Springer, 2019)
This textbook describes in detail the fundamental information about the 8051 microcontroller and it carefully teaches readers how to use the microcontroller to make both electronics hardware and software. In addition to discussion of the 8051 internals, this text includes numerous, solved examples, end-of-chapter exercises, laboratory and practical projects. Explains internals of 8051 hardware and relates to general principles of computer architecture; Demonstrates how to implement various electronics applications, with hardware and software design for 8051 microcontrollers; Includes numerous, solved examples, end-of-chapter exercises, laboratory and practical projects.